PROBLEMS IN THE MATERIAL AND TECHNICAL BASE OF SECONDARY SCHOOLS OF THE SOUTHERN REGIONS OF UZBEKISTAN IN THE YEARS OF INDEPENDENCE AND THEIR SOLUTION - Sharopova Nigora Akbarovna; Quvonova Ruxshona Komil qizi (Web of Journals Publishing, 2024)
This article explores the challenges faced by secondary schools in the southern regions of Uzbekistan concerning their material and technical infrastructure since the country's independence. It conducts a thorough analysis of existing literature, identifies key issues, and proposes solutions to improve the situation. Through a comprehensive examination, this study aims to contribute to the enhancement of educational facilities in these regions, thereby fostering better learning environments and opportunities for students.
Keywords: Uzbekistan, secondary schools, material and technical base, infrastructure, challenges, solutions.